The quest for a European strategic culture changing norms on security and defence in the European Union - Meyer, Christoph O. 1973- (Palgrave Macmillan, 2006)
The Quest for a European Strategic Culture investigates whether strategic norms and beliefs held in different countries have become more similar since 1989 and explores the implications for the viability of a common European Security and Defence Policy. The empirical evidence emerging from various sources shows some significant changes